Vulnerabilities of the Romanian economy generated by the foreign trade, the external debt and the exchange rate after Romania's accession to the European Union - Camelia Milea (Financial Studies, 2018)
The paper analyses the vulnerabilities which can be brought about by the structure and trend of the foreign trade and the external debt, and by the exchange rate to the Romanian economy, in the period after our country's accession to the European Union. The structure and the trend of the current account can represent a cause of vulnerabilities for the sustainability of each country's economy. Therefore, the present article analyses the Romanian current account and its characteristics. Based on these findings, the author draws some conclusions regarding the possible effects of the vulnerabilities induced by the current account. Also, the author analyses the structure of the Romanian external debt on maturities and on creditors and points out the possible vulnerabilities generated affecting the evolution of the economy. Finally, in the article it is analysed the stability of the Romanian leu/euro exchange rate in the context of Romania's goal to join the eurozone.
Keywords: F31; F32; F34; 330; current account deficit; national currency; stability; indebtedness